KALIMAT TERBELAH BAHASA INDONESIA: KEKHASAN STRUKTUR DAN KEBERMAKNAANNYA - Budiman, Arif (Sunan Kalijaga State Islamic University Yogyakarta, 2020)
This article aims to reveal the various patterns of cleft clause in Bahasa Indonesia and their meaning. The research data were taken from Indonesian translation of the Quran. The data here included all the cleft sentences in the source. They were then sorted and analyzed based on theories of cleft sentences of Indonesian and English. The results of the analysis show that the cleft sentences in Bahasa Indonesia are constructed in Predicate (P) – Subject (S), P-S-Adjunct (A), and P-A-S. In these patterns, the cleft sentences are the true cleft sentences. Besides, there are other constructions found, namely: S-P, S-P-A, A-S-P, and S-A-P. However, the sentences in the patterns make pseudo cleft. Both group are similar in terms of the elements and the presuposition they imply. The difference is only in the order in which the pseudo cleft put the focus at the back, or on the right side of the copula, which means the focused and its priority are slightly reduced. In Bahasa Indonesia, cleft sentence is not constituted by two clauses because its clefted constituent can stand by itself as a cleft noun/phrase (for example, “mereka”, “merekalah” or “adalah mereka”), without having to be put as a complement of a clause such as that of its English counterpart (“it is they”).